Essays on economic efficiency of commercial banks and economic effects of foreign bank presence - Manlagñit, Maria Chelo V. (ProQuest LLC, 2009)
This dissertation consists of three independent essays on the Philippine commercial banks from 1990 to 2006. The first essay examines the cost efficiency by incorporating risk and asset quality measures. Consistent with earlier studies, the results show substantial inefficiencies among domestic banks and that risk and asset quality affect the efficiency of the banks. The substantial increase in the inefficiency can be attributed to the adverse effects of the 1997 Asian financial crisis and the subsequent costs of banking reforms and regulatory changes which were enacted to stabilize and strengthen the sector. Macroeconomic instabilities, particularly banking crisis, could have distorted the incentive structure for banks, making resource allocation to achieve efficiency a more difficult task. The second essay investigates the profit efficiency and simultaneously identifies potential correlates that may explain differences in efficiency among banks. This study further examines separately the cost and revenue efficiencies of the banks to determine which of these efficiencies has the greater effect on profit efficiency. The findings suggest that profit efficiency is driven by both costs and revenues since profit efficient banks tend to be both cost and revenue efficient. Results also show that aside from banking reforms and adverse shocks to the economy, the factors that significantly affect the efficiency of the banks and thus, can help explain the differences in efficiency among banks, are the organizational structure and other bank-specific characteristics, particularly commercial bank type, whether a bank has undergone merger, and bank size. The third essay examines the economic effects of foreign bank presence. Results provide strong evidence on competition effects which lead to the reduction in the profitability and overhead costs of domestic banks. These findings, which reveal that both the actual market penetration and mere presence of foreign banks exert competitive pressure to domestic banks, imply that foreign banks serve as an effective competitive force, reducing the excess profits earned by domestic banks and compelling them to update their production technologies and techniques to improve their cost efficiency. The findings on competition effects in the domestic banking system justify the liberalization of foreign bank entry in the Philippines.--Abstract.